2021
DOI: 10.1186/s12913-021-06057-4
|View full text |Cite
|
Sign up to set email alerts
|

The Mitigating Toxic Stress study design: approaches to developmental evaluation of pediatric health care innovations addressing social determinants of health and toxic stress

Abstract: Background Health care administrators must establish and promote effective partnerships with community agencies to address social determinants of health, including reducing exposure of infants and young children to chronic stress. Because infants’ experiences are inextricably tied to their caregivers, an important target for mitigating “toxic” stress exposure in early childhood is through reducing parents’ experiences of chronic stress in addition to protecting children from direct experiences … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…For example, families that are less financially resourced or face other intersecting disadvantages by dint of a lack of social capital (e.g., single-parent status or racial and ethnic backgrounds as people of color) may respond to pandemic-related stress differently within the family. Exposure to heightened stress through inequities in the social determinants of health may constitute toxic stress that is associated with amplified transmission of negative experiences between parents and their children (McCrae et al, 2021). Conversely, resilience may be fostered through developing strong protective factors and adaptive responses over the course of prolonged experiences of disadvantage (Masten & Narayan, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…For example, families that are less financially resourced or face other intersecting disadvantages by dint of a lack of social capital (e.g., single-parent status or racial and ethnic backgrounds as people of color) may respond to pandemic-related stress differently within the family. Exposure to heightened stress through inequities in the social determinants of health may constitute toxic stress that is associated with amplified transmission of negative experiences between parents and their children (McCrae et al, 2021). Conversely, resilience may be fostered through developing strong protective factors and adaptive responses over the course of prolonged experiences of disadvantage (Masten & Narayan, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…This analysis examines qualitative interview data collected as a part of a mixed-methods rapid cycle study examining the impact of COVID-19 on families with young children. In that study, five counties had engaged in an innovation in early childhood and healthcare to address family access to concrete and social supports (McCrae et al, 2021). The last data collection wave for that study was concluded just as the global COVID-19 pandemic was beginning (Byers et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…This paper qualitatively examines eight clinics’ experiences implementing DULCE or I‐SCRN between 2017 and 2020. We use data collected as part of a longitudinal, mixed‐methods study of pediatric clinic‐ and community‐based approaches to prevent and mitigate stress among families with young children (McCrae et al, 2021). The study was approved by the University of Chicago Crown Family School of Social Work, Policy, and Practice and Chapin Hall Institutional Review Board.…”
Section: Methodsmentioning
confidence: 99%
“…Our study examines coordination between pediatric healthcare and community‐based early childhood providers among eight clinics that implemented two different organizational frameworks to address family social needs at well‐child healthcare visits. Clinics are located in five communities in three states and largely serve lower‐income, Medicaid‐insured families (McCrae et al, 2021).…”
Section: Introductionmentioning
confidence: 99%